Sistem Informasi Pengarsipan Berbasis Web Mengunakan Algoritma Levenshtein Distance - achmad noeman; Agus Hidayat; Arif R. Dwiyanto; Mohammad Hoki Rezky (Jurnal Riset Informatika dan Teknologi Informasi, 2026)
This study proposes the development of a web-based archiving information system at PMI Jakarta City, supported by the Levenshtein Distance algorithm as the core feature for document retrieval. The system is designed to overcome the limitations of manual archiving methods, such as restricted search capabilities, potential recording errors, and the risk of losing physical records. By adopting the Waterfall approach, the research was conducted through several stages: requirements analysis, interface design, implementation, and system testing. The results demonstrate that the Levenshtein Distance algorithm effectively improves the accuracy of document searches, even when spelling variations or typographical errors occur in the query. This makes the system more adaptive and efficient compared to traditional manual methods. Furthermore, the implementation of a web-based system reduces reliance on physical archives, enhances storage security, and accelerates information access. Overall, the developed system provides a practical and modern solution to support document management at PMI Jakarta City.